De objetos a “patrimonio moral de la nación” - María Elida Elida Blasco (Centre de Recherches sur les Mondes Américains, 2012)
This article summarizes certain aspects connected with the construction of the notion of cultural heritage in Argentina during the first half of the XX century. Firstly, the authors will review the collection of initiatives during the first two decades of the XX century which attempted to call the attention of the government representatives to the need of establishing certain mechanisms to protect those objects which had been considered historically interesting. The organization of collections and the establishment and operation of the so-called historical museums fall within this context. Secondly, the authors will describe the context in which a peculiar manner of representing and recreating the national history and, particularly, the historical moments in which the Argentinian nationality is considered to have been founded, gained popularity within diverse exhibition spaces in the mid 1930s. Finally, the authors will review the process whereby certain government agencies were founded in a context in which the historiographical field was being consolidated. Such organisms were in charge of determining which material remains to preserve as testimonies of the national history and establish the body of law by means of which they would be established as the country’s moral heritage.